“WHAT’S UP, GUYS?” KHAIRUL AMING ON TWITTER: THE SOCIAL MEDIA INFLUENCER ROLE IN SHAPING USERS’ OPINION AND DECISION ON COVID-19 VACCINATION - Nur Ayuni Mohd Jenol; Nur Hafeeza Ahmad Pazil; Nor Hafizah Selamat (Journal of Islamic, Social, Economics and Development, 2023)
Influencers seem to be endowed with a certain amount of social capital. Social media influencers (SMIs) position in their social network provides them with the legitimacy and credibility to mobilise societal decisions and behaviours. This study aims to explore the topic of discussion shared by Khairul Amin, one of the prominent Malaysian social media influencers, on Twitter, regarding COVID-19 vaccine. This study conducted a content analysis using Twitter API to determine the presence of specific phrases or concepts among tweets about COVID-19 immunisation and the discussion held by Khairul Aming on Twitter. Based on the findings, it can be seen how he influences other users' opinions and vaccination decisions. As he plays an active role specifically during the early period of COVID-19 vaccination, he is optimistic to educate other users about vaccination and encourage them to be vaccinated. Khairul Aming not only discuss his thoughts, feelings, and beliefs on the COVID-19 vaccine, but also frequently share his own experiences. Such affective information, authentic and genuine content is more likely to be valued, attracts attention, and emotion as well as prompts society positive evaluation, thereby increasing the content’s persuasiveness.